PELATIHAN KEWIRAUSAHAAN DENGAN MEMBUAT BUKET SNACK DAN ES KRIM ANEKA RASA SEBAGAI ALTERNATIF BUAH TANGAN BAGI SISWA SMP NEGERI 1 PALEMBANG KECAMATAN BUKIT KECIL KOTA PALEMBANG - Fajar Sari, Dian Novita (Jurnal Semarak Mengabdi, 2024)
The community service carried out by students of SMP Negeri 1 is part of the entrepreneurship training in making snack bouquets and various flavors of ice cream as an alternative souvenir, where later with this innovation in making snack bouquets, students can develop the entrepreneurial spirit. This activity was attended by 38 students of SMP Negeri 1, Bukit Kecil District, Palremabng City for approximately 5 hours, where the initial activity was an entrepreneurship seminar from an entrepreneurship and marketing lecturer, then practice and training in making bouquets of snacks and ice cream of various flavors using waste paper as a buffer material. bouquet to make it more economical. The end result of this activity is that the students are proficient and can be creative on their own to develop their talents and skills in making snack bouquets and various flavors of ice cream so that they can have high selling points and create new innovations so that consumers don't feel bored with the same bouquets.